HIV Genomic Mutations Causing Resistance to Antiretroviral Drugs in Seropositive Sicilians - Paola Bertuccio, Maria; Picerno, Isa; Maurizio Celesia, Benedetto; Galvagna, Salvatore; Sturniolo, Giuseppe; Spataro, Pasquale; Visalli, Giuseppa (Current HIV Research, 2014)
Through the use of highly active antiretroviral therapy a significant reduction occurred in mortality and morbidity caused by Human Immunodeficiency Virus. The use of antiretroviral drugs resulted in the emergence of resistant viral strains due to mutations that cause a selective advantage to the virus. The aim of our study is to monitor the HIV-1 infection in Sicilians patients evaluating the presence of mutations that make the virus resistant to the therapy. The QIAGEN QIAamp Viral RNA Mini Kit was used to extract HIV-1 viral RNA from 300 patients while the TRUGENE HIV-1 Genotyping Kit and the OpenGene DNA Sequencing System determined viral mutations in the RNA samples. The analysis showed that from 300 subjects, 116 developed Antiretroviral Drug Resistance. The percentage of patients with resistance to nucleoside reverse transcriptase inhibitor (NRTI), non nucleoside reverse transcriptase inhibitor (NNRTI) and protease inhibitor was 26%, 23% and 20%, respectively. Comparison between drug resistances and mutations showed that 134 individuals had mutations in genes codifying for reverse transcriptase but a little more than 50% were associated with resistance to reverse transcriptase inhibitors, in particular 78 and 68 subjects developed drug resistances to NRTI and NNRTI classes respectively. Subjects that showed mutations in genes codifying for protease were 216 but only 59 of these were associated with resistance to protease inhibitors. Our findings emphasize the importance of continued resistance surveillance. Monitoring of transmitted resistance continues to be needed among treatment-exposed patients because of the benefit it provides for the development of drugs effective against the most frequently found drug-resistant viruses.
Keywords: Sicilians